A high-performance photo-microbial desalination cell. (1st June 2016) - Liang, Yuxiang; Feng, Huajun; Shen, Dongsheng; Li, Na; Long, Yuyang; Zhou, Yuyang; Gu, Yuan; Ying, Xianbin; Dai, Qizhou
Abstract: This paper introduces a high-performance photo-microbial desalination cell (PMDC) based on photo-electrochemical interactions. The anode of the cell was successfully modified with nanostructured α-Fe2 O3 . The maximum current density of the PMDC during operation was 8.8 A m −2 at an initial salt concentration of 20 g L −1, which was twice that of the unmodified microbial desalination cell. The results of electrochemical impedance spectroscopy and cyclic voltammetry indicated the current increase of PMDC was mainly contributed by the high electron transfer rate at electrode/biofilm interface. The salt concentration of the effluent from the middle chamber was below ca. 1.4 mg L −1 and the salt removal performance of the PMDC was always higher than 96%. The calculated number of harvested electrons agreed well with NaCl removal. In conclusion, the present PMDC effectively offers simultaneous electricity generation and desalination.